Chemical Bonding Configurations at the Interface of SiO2/Si(111) - Bahari, A.; Suzban, M.; Rezai, L.; Rezai, M.; Roodbari, M.; Morgen, P. (Asian Journal of Chemistry, 2010)
The interface and near interface regions of SiO2/Si and related films have received attentions for several decades. Silicon dioxide has been used as a realistic gate dielectric material in complementary metal-oxidesemiconductor (CMOS) components because the interface between silicon dioxide and silicon substrate is amorphous. In the present work, ultra thin silicon dioxide (below one nm) films have been grown on Si(111) at 700 ºC and the chemical bonding configurations of interface states between silicon dioxide and silicon substrate have been investigated with synchrotron radiation induced photoelectron spectroscopy.